Pengaruh Fasilitas Kerja (Berupa Pembukaan Gedung Baru, Perbaikan Interior Dan Layout) dan Motivasi Kerja Karyawan terhadap Kepuasan Kerja Karyawan di Rumah Sakit Muhammadiyah Taman Puring - Furqan, Purnama Alam (UHAMKA Graduate School Thesis Abstract Collection, 2016)
The aims of this thesis is to test whether there is an effect of work facilities (in the form of opening the new building, upgrading the interior and layout) and employee?s work motivation toward employee?s job satisfaction in Muhammadiyah Taman Puring Hospital (MTPH). The method of this research was causal survey using path analysis. The data was analyzed using descriptive statistics and inferential statistics. Descriptive analysis was used to determine the frequency distribution, total score, average score, standard deviation, mode, median, maximum score and minimum score, and illustrated by histogram. Inferential statistical was performed by calculating and testing the correlation coefficient (r), coefficient of determination (R2), and path coefficient (p).The result of this research shows that: There is a positive and significant direct effect of work facilities toward employee?s job satisfaction, with a correlation coefficient (r13) of 0.570, coefficient of determination (R2) of 0.325 and path coefficient (P31) of 0.187. Work facilities have relative contribution of 32.50% on employee?s job satisfaction, while the remaining of 67.5% is determined by the variable of work motivation and other variables which are not included within the scope of research. There is a positive and significant direct effect of employee?s work motivation toward employee?s job satisfaction, with a correlation coefficient (r23) of 0.686, coefficient of determination (R2) of 0.471 and path coefficient (p32) of 0.558. Employee?s work motivation has relative contribution of 47.10% on employee?s job satisfaction, while the remaining of 52.9% is determined by the variable of work motivation and other variables which are not included within the scope of research. There is a positive and significant direct effect of work facilities toward employee?s work motivation, with a correlation coefficient (r12) of 0.687, coefficient of determination (R2) of 0.472 and path coefficient (p21) of 0.687. Work facilities give relative contribution of 47.20% on employee?s job satisfaction, while the remaining of 52.8% is determined by other variables which are not included within the scope of research.Based on the research result, it is suggested that the MTPH enhancing and/or make improvements to the room?s appearance in terms of interior and layout in order to be more comfortable to employees and more functional as intended. This condition will increase employee?s work motivation and/or employee?s job satisfaction.